Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

H(x)=3x-2; find H(-1)

Sagot :

Step 1: Write out the function

[tex]H(x)=3x-2[/tex]

Step 2: Compute H(-1)

To find H(-1), we will replace wherever we find x in the function with (-1).

This is called substitution

[tex]H(-1)=3(-1)-2[/tex]

3(-1) means 3 × -1 which gives -3,

Therefore,

[tex]H(-1)=-3-2[/tex]

-3 - 2 gives -5,

Hence,

[tex]H(-1)=-5[/tex]

Therefore, H(-1) = -5